THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE AND ATTITUDES RELATED PERSONAL HYGIENE OF FEMALE ADOLESCENTS AT DAYAH INSAN QUR'ANI, SUKAMAKMUR, THE DISTRICT OF ACEH BESAR - Ramli, Nurlaili; Hayatun Nufus; anita; Gustiana (Journal of Midwifery and Community Health (JMCH), 2024)
Background: A lack of personal hygiene among adolescents can lead to various health problems, particularly reproductive health problems. Providing information through education related to knowledge about personal hygiene is one way to help adolescents maintain their personal hygiene. Subjects and Method: This study's subjects were 65 female students at Dayah Insan Qurani. The sampling technique used was simple random sampling from 7th—and 8th-grade students. The independent variable was the level of knowledge, and the dependent variable was adolescents' attitudes toward personal hygiene. The analysis was univariate and bivariate with a Chi-Square test using SPSS version 25 software. Results:  The level of knowledge among the adolescent girls at Dayah Insan Qurani was good at 35.4%, while the negative attitudes were at 56.9%. The results of the bivariate test indicated that female adolescents with good knowledge had a positive attitude of 65.2%, while those with negative attitudes were at 34.8% with a p-value of 0.012. Conclusion: Female adolescents with a good level of knowledge tend to have positive attitudes compared to those with less knowledge. It is hoped that the roles of parents, teachers, and peers can enhance education for adolescents through various media, enabling them to possess good knowledge and positive attitudes regarding personal hygiene.